GEF in Africa : How the Global Environmental Facility is Working with African States for a Sustainable Future - Global Environment Facility (Washington, DC, 2013)
This report reviews the collaboration between the Global Environmental Facility (GEF) and the African states. Since 1991 GEF has financed 425 projects to address global environmental problems through sustainable development in more than 50 African countries. This report specifically reviews the GEF's works with African countries on key natural resource issues : land degradation, forests, fresh water resources, marine and coastal areas, energy, and persistent organics pollutants. Readers will also gain a better understanding of how GEF works with countries to assure that the project development process is country-driven and reflects national development priorities. GEf has gained valuable experience working on environmental challenges facing the African continent. In the years ahead, GEF looks forward to continue to work with governments, local communities, NGOs, the private sector, and bilateral and multilateral organization in Africa. Together, we can promote effective problem-solving partnerships and practical solutions to help improve the global environment while creating livelihoods and opportunities for the world's poor.